2019
DOI: 10.1111/jmcb.12619
|View full text |Cite
|
Sign up to set email alerts
|

On the Value of Virtual Currencies

Abstract: Our economic framework suggests that the exchange rate of virtual currency is determined by three components. First, the current value of transactions in virtual currency which absorb part of the exchange rate risk. Second, the decisions and expectations of forward-looking investors to buy virtual currency (thereby effectively regulating its supply). Third, the elements that jointly drive future consumer adoption and merchant acceptance of virtual currency. The model predicts that, as virtual currency becomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 38 publications
(38 reference statements)
0
54
0
Order By: Relevance
“…Hayes (2017) advocates the cost of production view on cryptocurrency pricing; yet, as we discussed earlier, from a market equilibrium perspective, being sunk cost (as in Dwyer 2015), it does not matter for the pricing of existing coins. 14 A concurrent work by Bolt and Van Oordt (2019) outlines three key elements of the cryptocurrency value: convertibility into fiat money or ability to buy goods and services, investors' expectations, and factors that determine acceptance of the cryptocurrency in the future, by both vendors and buyers. Simultaneously, Schilling and Uhlig (2019) offer a model where cryptocurrencies are a reliable medium of exchange and compete against fiat money: this role implies the current price of cryptocurrencies is the expectation of their future value (a martingale), yet interestingly, competition and substitutability between the two imply in their analysis cryptocurrencies should disappear in the long run equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…Hayes (2017) advocates the cost of production view on cryptocurrency pricing; yet, as we discussed earlier, from a market equilibrium perspective, being sunk cost (as in Dwyer 2015), it does not matter for the pricing of existing coins. 14 A concurrent work by Bolt and Van Oordt (2019) outlines three key elements of the cryptocurrency value: convertibility into fiat money or ability to buy goods and services, investors' expectations, and factors that determine acceptance of the cryptocurrency in the future, by both vendors and buyers. Simultaneously, Schilling and Uhlig (2019) offer a model where cryptocurrencies are a reliable medium of exchange and compete against fiat money: this role implies the current price of cryptocurrencies is the expectation of their future value (a martingale), yet interestingly, competition and substitutability between the two imply in their analysis cryptocurrencies should disappear in the long run equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…They argue that this means that financial regulations including knowyour-customer regulations can have a non-negligible impact on the bitcoin market. Bolt and Oordt (2016) develop an economic framework to investigate the exchange rate of a virtual currency. Their model shows that the exchange rate will become less sensitive to the impact of speculative behaviour with more widespread use of the virtual currency.…”
Section: Cryptocurrencies: Economicsmentioning
confidence: 99%
“…Studies of the drivers of Bitcoin prices have often concluded that speculation is one of, or even the main, driver, [4][5][6][7][8][9] and this is partly driven by publicity, both negative and positive, which is partly spread by social media. 10 With the value of Bitcoin changing so much it is not surprising that it is hard to find goods and services with an advertised price in BTC, even if BTC is an acceptable form of payment.…”
Section: Cryptocurrency Performance As Moneymentioning
confidence: 99%